Suppression of two tungro viruses in rice by separable traits originating from cultivar Utri Merah - Encabo, Jaymee R.; Cabauatan, Pepito Q.; Cabunagan, Rogelio C.; Satoh, Kouji; Lee, Jong-Hee; Kwak, Do-Yeon; De Leon, Teresa B.; Macalalad, Reena Jesusa A.; Kondoh, Hiroaki; Kikuchi, Shoshi; Choi, Il-Ryong (Scientific Societies, 2009)
Rice tungro disease (RTD) is caused by Rice tungro spherical virus (RTSV) and Rice tungro bacilliform virus (RTBV) transmitted by green leafhoppers. Rice cv. Utri Merah is highly resistant to RTD. To define the RTD resistance of Utri Merah, near-isogenic lines (NIL, BC5 or BC6) developed from Utri Merah and susceptible cv. Taichung Native 1 (TN1) were evaluated for reactions to RTSV and RTBV. TW16 is an NIL (BC5) resistant to RTD. RTBV was able to infect both TN1 and TW16 but the levels of RTBV were usually significantly lower in TW16 than in TN1. Infection of RTSV was confirmed in TN1 by a serological test but not in TW16. However, the global gene-expression pattern in an RTSV-resistant NIL (BC6), TW16-69, inoculated with RTSV indicated that RTSV can also infect the resistant NIL. Infection of RTSV in TW16 was later confirmed by reverse-transcription polymerase chain reaction but the level of RTSV was considerably lower in TW16 than in TN1. Examination for virus accumulation in another NIL (BC6), TW16-1029, indicated that all plants of TW16-1029 were resistant to RTSV, whereas the resistance to RTBV and symptom severity were segregating among the individual plants of TW16-1029. Collectively, these results suggest that RTD resistance of Utri Merah involves suppression of interacting RTSV and RTBV but the suppression trait for RTSV and for RTBV is inherited separately.